Penguatan Kesadaran Masyarakat dalam Mengenal Risiko Kesehatan di Balik Gaya Hidup Paylater - Noerma Kurnia Fajarwati; Ayu Sabila; Wulan Safitri; Resti Sughiarti; Wahyu Winda Asmara; Fahri Hafidz; Rizki Amilia; Hernawati Hernawati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
PayLater services are becoming increasingly popular among the public, offering convenience and flexibility in meeting daily needs and lifestyle demands. However, uncontrolled use has the potential to cause financial problems that significantly impact both mental and physical health. This community service activity aims to increase the understanding of community leaders regarding healthy financial management and the health risks that may arise from a PayLater-based consumer lifestyle. The outreach program was conducted by KKM students from Bina Bangsa University Group 22 in Banjar Negara Village, Ciwandan District, Cilegon City, with 30 participants consisting of local RT and RW heads. Methods used included interactive lectures, discussions, and question-and-answer sessions that encouraged active participation and contextual sharing of experiences. The results of the activity showed an increase in participants’ awareness of the importance of financial literacy as an integral part of maintaining overall quality of life. Participants recognized that financial health is closely related to mental well-being, as excessive financial pressure can trigger stress, anxiety, and even chronic illnesses. The program also emphasized practical strategies such as budgeting, distinguishing needs from wants, and limiting PayLater use to essential needs only. It is expected that RT and RW heads who have participated can act as educational agents in their communities, spreading financial literacy and awareness of health risks. In the future, similar programs need to be expanded to other community groups, supported by digital media and cross-sector collaboration to create a financially independent and physically and mentally healthy society.